Analysis of Risk Factors for Perioperative Complications Following Open and Laparoscopic Nephrectomy in Patients with Non-Functioning Kidneys: A Retrospective Cohort Study - Raedi Ardlo Luzman; Ahmad Zulfan Hendri (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Non-functioning kidneys are a common indication for nephrectomy, especially in resource-limited settings. Minimally invasive nephrectomy is preferred over open surgery because it reduces perioperative morbidity; however, how patient-related factors such as anemia, body mass index, and immunonutritional markers affect complication risk remains poorly defined. This retrospective cohort study examined perioperative outcomes and predictors of complications in 44 patients who underwent nephrectomy for non-functioning kidneys at a tertiary center in Indonesia between January 2022 and October 2025. Laparoscopic nephrectomy was used in 68% of cases, with markedly lower intraoperative blood loss (median 150 vs. 500 cc; approximately 73% reduction), a shorter median hospital length of stay (3 vs. 4.5 days), and earlier drain removal (3 vs. 4 days) compared with open surgery. These results align with prior studies highlighting laparoscopy's benefits in reducing morbidity and expediting recovery. Overall, 32% of patients experienced intra- or postoperative complications. Open nephrectomy significantly increased the risk of complications (OR 4.0, p=0.049). Preoperative anemia (OR 8.7, p=0.006) and underweight status (OR 11.7, p=0.001) emerged as primary risk factors, emphasizing the importance of transfusion needs and the adverse nutritional impacts across major surgical interventions. In contrast, a high neutrophil-to-lymphocyte ratio, a high platelet-to-lymphocyte ratio, and a low prognostic nutritional index despite being commonly observed were not significantly associated with perioperative complications in this retrospective cohort. For benign nephrectomy addressing non-functioning kidneys, the most effective approach to curbing perioperative complications is to prioritize laparoscopic surgery coupled with systematic management of anemia and undernutrition Keywords: Nephrectomy, Perioperative Complication, Inflammatory Marker, Body Mass Index